PREVALENCE AND IMPACT OF DENTOALVEOLAR TRAUMA IN CHILDREN AND ADOLESCENTS: A DETAILED ANALYSIS - Jesus da Silva, Bruna; de Sousa Ribeiro, Dilmar; Carlos da Silva, Erika; Maria de Amorim Santos, Eva; Andrade Lira, Felipe; Moreira Vargas, Larissa; de Souza Pereira, Malvina; Natágoras Alves de Albuquerque, Marcone; César Ribeiro da Silva Filho, Paulo; Thainá Oliveira dos Santos Silva, Sabrina (Health and Society, 2023)
The study addresses the prevalence and impact of dentoalveolar traumas in children and adolescents. These traumas rank second among the most common accidents in this age group and are gaining increasing global attention due to associated physical and psychological implications. Detailed clinical assessment, along with radiographic examinations, is crucial for accurate diagnosis and the selection of appropriate treatment. Dental traumas often affect the supporting dental tissues, with varying degrees of severity, ranging from subtle cracks in the dental enamel to more severe injuries such as luxations and avulsions, which can also involve damage to surrounding bone structures. These traumas are one of the main causes of tooth loss in children, especially the upper anterior teeth, with a wide variation in incidence. Causes range from accidental falls to sports activities and other events. For rapid and accurate diagnosis, it is important to conduct a methodical assessment of patients, considering incident details and possible associated symptoms. Proper treatment performed by dental surgeons is crucial to prevent irreversible damage. The study also discusses the classification of traumatic dental injuries, encompassing different types of fractures and displacements, both in dental tissues and supporting structures. Pulp necrosis is one of the main consequences of these traumas, which can have aesthetic, psychological, and social impacts, in addition to implying significant costs. Immediate care is important, but long-term follow-up is often necessary. In summary, the study emphasizes the importance of dentoalveolar traumas in children and adolescents, highlighting their prevalence, classification, and implications. It also underscores the need for proper diagnosis and treatment, as well as the importance of long-term follow-up to minimize the adverse effects of these injuries.